Finding God in All Things: A Dialogue between the "Bhagavad Gita" and the "Spiritual Exercises of Ignatius" - Michael, Pavulraj (Studies in interreligious dialogue, 2018)
The dialogue between the Bhagavad Gita and the Spiritual Exercises on "Finding God in All Things" (Isavasyam idam sarvam and Hallar Dios en todas las cosas) points toward a meeting of heart and mind between Hinduism and Christianity. The essence of the spirituality of the Bhagavad Gita, like the essence of the spirituality of Ignatius, is the vision of God in all things and all things in God, and, for the same reason, its spirituality is oriented to God above the world as well as within it. Both the Bhagavad Gita and the Spiritual Exercises agree that only those who have found God above the visible world are able to find God in all things, and vice-versa. The quest to find God in all things is an exercise involving conscious effort and constant attentiveness. This quest requires a fundamental receptivity toward the Truth who guides the steps of humanity.